2021
DOI: 10.1002/jcp.30351
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin ameliorates early brain injury after subarachnoid hemorrhage via inhibition of pyroptosis and neuroinflammation

Abstract: Subarachnoid hemorrhage (SAH) is a subtype of stroke with high mortality and morbidity due to the lack of effective therapy. Atorvastatin has been reported to alleviate early brain injury (EBI) following subarachnoid hemorrhage (SAH) via reducing reactive oxygen species, antiapoptosis, regulated autophagy, and neuroinflammation. Which was the related to the pyroptosis? Pyroptosis can be defined as a highly specific inflammatory programmed cell death, distinct from classical apoptosis and necrosis. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 50 publications
(81 reference statements)
2
59
0
Order By: Relevance
“…A number of previous studies have demonstrated that SAH-induced brain injury can be alleviated by modulating ROS and caspase-dependent neuronal death ( 31-33 ). In agreement with a previous study, brain edema and cortical neuronal pyroptosis was observed in a SAH model, where the pathologic changes may be attributed to deficits in neurologic function ( 34 ). In addition, it was also shown that brain edema occurred on bilateral hemisphere regardless of the perforation side ( 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…A number of previous studies have demonstrated that SAH-induced brain injury can be alleviated by modulating ROS and caspase-dependent neuronal death ( 31-33 ). In agreement with a previous study, brain edema and cortical neuronal pyroptosis was observed in a SAH model, where the pathologic changes may be attributed to deficits in neurologic function ( 34 ). In addition, it was also shown that brain edema occurred on bilateral hemisphere regardless of the perforation side ( 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…The severity of brain edema was evaluated by measuring the brain water content using the standard wet-dry method, as previously reported ( 15 , 33 , 34 ). The mice were sacrificed 72 h following ICH, and the entire brain was harvested and separated into the ipsilateral and contralateral cortex, ipsilateral and contralateral basal ganglia, and cerebellum (wet weight).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were then washed in prewarmed PBS (37°C) and assessed by an MTT assay as per the manufacturer's instructions (Promega Corporation). As determined in a prior study ( 15 ), neurons were stimulated with 80 mM hemin for 72 h to mimic intracranial hemorrhage conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, previous studies indicated that NLRP3 in ammasome could activate caspase-1 and promote the secretion of proin ammatory cytokines (IL-1β and IL-18) (Kelley, et al 2019). Pyroptosis, which was activated by IL-1β and IL-18, was implicated to induce neuroin ammation in SAH-induced EBI (Chen, et al 2021). Our study showed that the application of 3K3A-APC and the inhibition of NLRP3 could signi cantly reduce the level of IL-1β and IL-18 as well as the proportion of pyroptosis cells in SAH rat and cell models.…”
Section: Discussionmentioning
confidence: 99%